The Active for Life Year 5 (AFLY5) school-based cluster randomised controlled trial: effect on potential mediators. (December 2015) - Lawlor, Debbie; Howe, Laura; Anderson, Emma; Kipping, Ruth; Campbell, Rona; Wells, Sian; Chittleborough, Catherine; Peters, Tim; Jago, Russell
Abstract Background Active for life year 5 (AFLY5) is a school-based intervention, based on social cognitive theory, which aims to promote healthy levels of physical activity and healthy eating by improving a child's self-efficacy to make healthy choices, their knowledge of how to make such choices and prompting parents to support their children to make healthy choices. Previously published results showed no effect on the three primary outcomes and beneficial effects on three of nine secondary outcomes (time spent screen-viewing at weekends, consumption of snacks and of high energy drinks). This paper aims to determine the effect of the intervention on potential mediators. Methods We conducted a cluster RCT of a school-based intervention, with allocation concealed by use of a remote system. The study was undertaken in the South West of England between 2011 and 2013. Participants were school children who were age 8–9 years at baseline assessment and 9–10 years during the intervention. Potential mediators were assessed at the end of the intervention. The intervention consisted of teacher training, provision of all materials required for lessons and homeworks and written materials for school newsletters and parents. The ten potential mediators were child-reported self-efficacy for physical activity and fruit and vegetable consumption, perceived parental logistic support and modelling for their child's physical activity, parental efforts to limit their child's sedentary behaviour and modelling of healthy fruit and vegetable consumption, together with a knowledge assessment. Results We successfully recruited 60 schools with over 2, 221 children; valid data for the 10 mediators were available for 87 % to 96 % of participants. Three of the ten potential mediators were greater in the intervention, compared with the control group: fruit and vegetable self-efficacy 2.2 units (95 % CI: 0.7 to 3.8), assessed on a scale 26 to 130; child-reported maternal limitation of sedentary behaviour 0.5 (0.1 to 0.8), scale 4 to 16; and knowledge 0.5 (0.2, 0.7) scale 0 to 9. Reported maternal limitation of sedentary behaviour and the child's knowledge explained 23 % of the effect of the intervention on reducing time spent on sedentary behaviour at the weekend. There was no effect on other mediators. Conclusions Our findings suggest that the effect of the AFLY5 intervention on reducing screen-viewing at weekends was partially mediated by an effect on mothers limiting their child's time spent sedentary and on increasing the child's knowledge about healthy behaviour. However, overall our findings suggest that theory driven interventions, like AFLY5, can fail to influence most potential mediators and this may explain the failure of the intervention to improve most primary and secondary outcomes. Trial registration Current Controlled TrialsISRCTN50133740 . Registered 17/03/2011